Semantics of the Color Term хар ‘Black’ in Folklore Texts: A Linguoculturological Aspect (A Case Study of Kalmyk Folktales Recorded by G. J. Ramstedt) - Aleksandra T. Bayanova (Монголоведение, 2021)
Introduction. The article analyzes semantic components and variants of the Kalmyk color term хар ‘black’ in folklore texts. Goals. The study investigates semantics of the color term хар ‘black’ in a linguocultural perspective. Materials. The work explores Kalmyk folktales recorded by the Finnish scholar G. J. Ramstedt during his scientific expedition to the Kalmyk Steppe. Results. The analysis reveals six shades of black and sums up its semantic constituents and variants. Special emphasis is laid on the applied Kalmyk-to-German translation means. Conclusions. The lexeme хар ‘black’ is distinguished by extensive semantics. It serves to denote animal coat and human skin colors. In personal names, it has the meaning of ‘strong, enduring’. The word can also identify an individual’s social status, e.g., хар яста күн ‘commoner’ (lit. ‘a black-boned man’). In most cases the lexeme хар ‘black’ contains negative connotations. The color black designates chthonian symbols (хар цурх ‘black pike’, хар темән ‘black camel’, ут хар күн lit. ‘tall (long) black man’).